2007
DOI: 10.1117/12.715740
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive sensors for smart textiles

Abstract: We have used inkjet printing to deposit silver conducting lines and small PEDOT (conducting polymer) sensors onto fabrics. The printed conductors penetrate into the fabric and can be shown to coat the individual fibers within the yarn, through the full thickness of the cloth. The PEDOT sensor has a resistance in the region of a few kilo-ohms and is connected to measuring equipment by printed silver lines with a resistance of a few ohms. In this way, local strains can be measured at different sites on a fabric.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…As the fibrous material is strained, the network creates more contacts, which decreases the resistance in the printed material resulting in a negative gauge factor. Al-Chami and Cretu reported a gauge factor of −81 for strains below 0.015% for PEDOT:PSS printed on paper [16], and Calvert et al reported gauge factors in the range of −5 to −20 for PEDOT printed on fabrics [15]. On the other hand, strain sensors fabricated using lift-off processes have exhibited less of a piezoresistive effect due to the increase in film thickness.…”
Section: A Cyclic Loadingmentioning
confidence: 96%
See 2 more Smart Citations
“…As the fibrous material is strained, the network creates more contacts, which decreases the resistance in the printed material resulting in a negative gauge factor. Al-Chami and Cretu reported a gauge factor of −81 for strains below 0.015% for PEDOT:PSS printed on paper [16], and Calvert et al reported gauge factors in the range of −5 to −20 for PEDOT printed on fabrics [15]. On the other hand, strain sensors fabricated using lift-off processes have exhibited less of a piezoresistive effect due to the increase in film thickness.…”
Section: A Cyclic Loadingmentioning
confidence: 96%
“…Among the strain sensitive materials, PEDOT:PSS has received attention as a good candidate for producing low cost printed strain sensors due to the material's inherent piezoresistive characteristics. For example, solution-processed PEDOT:PSS has been used to create strain sensors by inkjet printing on textiles [15], paper [16], and plastics [16], [17]. Although PEDOT:PSS exhibits piezoresistive characteristics, the material also has several drawbacks caused by environmental dependency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEDOT:PSS is a transparent, conjugated and conductive polymer that is highly ductile, stretchable, and has good environmental stability. Several researchers have fabricated and characterized tactile sensors using PEDOT:PSS for smart textiles [5] flexible piezoresistive strain gauge sensors [6.7] and touch sensors [8]. Its success as a sensing material can be attributed to its gauge factor, 5 to 20, whereas that of conventional metal films is about 2.…”
Section: Pressure Sensors For Robotic Skinsmentioning
confidence: 99%
“…PEDOT:PSS is a conductive and transparent polymer that is stretchable, highly ductile and environmentally stable [29]. It has been used as smart textiles [21], flexible piezoresistive strain gauge sensors [22][23] and touch sensors [24]. Typical conventional metal films has a gauge factor of 2, PEDOT:PSS's gauge factor ranges from 5 to 20, makes it an ideal choice for our work.…”
Section: Piezoresistive Pressure Sensormentioning
confidence: 99%